Not Bad: Passive Leg Raising in Cardiopulmonary Resuscitation-A New Modeling Study - Zhang, Yanru; Jiménez-Herrera, María; Axelsson, Christer; Cheng, Yunzhang (Frontiers in Physiology, 2017)
Aim: To evaluate, using a simulated haemodynamic circulation model, whether passive leg raising (PLR) is able to improve the effect during cardiopulmonary resuscitation (CPR); to expose the possible reasons why PLR works or not. Materials and Methods: We adapted a circulatory model for CPR with PLR. First we compared cardiac output (CO), coronary perfusion pressure (CPP), blood flow to heart (Qheart), and blood flow to neck and brain (Qhead) of standard chest compression-only CPR with and without PLR; second we simulated the effects of PLR in different situations, by varying the thoracic pump factor (TPF) from 0 to 1; third we simulated the effects when the legs are lifted to the different heights. Finally, we compared our results with those obtained from a published clinical study. Results: According to the simulation model, 1) When TPF is in the interval [0,1), CPP, CO, Qheart and Qhead are improved with PLR, among them with half-thoracic/half-cardiac pump effect (TPF is 0.5), CPP, CO, Qhead and Qheart increase the most (by 14%, 14%, 15%, and 17%). 2) When TPF is 1 (pure thoracic pump, with an emphysema or extremely thick thorax), PLR has almost no effect on CPP, CO and Qheart (-1%, 2% and 0), whereas Qhead is increased by 9%; 3) Regardless of whether there is a cardiac or thoracic pump effect, PLR is able to increase Qhead by 9% to 15%. 4) When the legs are lifted to 30 degree to the ground, the volume transferred from legs to upper body is 36% of the initial volume in legs; when the legs are lifted to 45 degree, the volume transferred is 43%; when the legs are lifted to 60 degree, the volume transferred is 47%; when the legs are lifted to 90 degree, the volume transferred is 50%. Conclusion: Generally PLR is able to achieve improved cerebral perfusion and coronary perfusion. In some extreme situations, it has no effect on cardiac output and coronary perfusion, but still improves cerebral perfusion. PLR could be a beneficial supplement to CPR, and it is not necessary to lift the legs too high above the ground.